PyCFTBoot: A Flexible Interface for the Conformal Bootstrap (Communications in Computational Physics, 2019)
We introduce PyCFTBoot, a wrapper designed to reduce the barrier to entryin conformal bootstrap calculations that require semidefinite programming. Symengineand SDPB are used for the most intensive symbolic and numerical steps respectively.After reviewing the built-in algorithms for conformal blocks, we explain how to usethe code through a number of examples that verify past results. As an application, weshow that the multi-correlator bootstrap still appears to single out the Wilson-Fisherfixed points as special theories in dimensions between 3 and 4 despite the recent proofthat they violate unitarity.
Keywords: CFT; conformal bootstrap; python; semidefinite programming.